2015
DOI: 10.1016/j.ajhg.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Heimler Syndrome Is Caused by Hypomorphic Mutations in the Peroxisome-Biogenesis Genes PEX1 and PEX6

Abstract: Heimler syndrome (HS) is a rare recessive disorder characterized by sensorineural hearing loss (SNHL), amelogenesis imperfecta, nail abnormalities, and occasional or late-onset retinal pigmentation. We ascertained eight families affected by HS and, by using a whole-exome sequencing approach, identified biallelic mutations in PEX1 or PEX6 in six of them. Loss-of-function mutations in both genes are known causes of a spectrum of autosomal-recessive peroxisome-biogenesis disorders (PBDs), including Zellweger synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 47 publications
7
117
0
Order By: Relevance
“…Although amelogenesis imperfecta discriminates between the two conditions this does not become apparent until the eruption of the secondary dentition. Retinal pigmentation is an inconsistent feature of were indicated with green frame (Ratbi et al, 2015). The mutation identified in this study was indicated with red frame.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 64%
See 4 more Smart Citations
“…Although amelogenesis imperfecta discriminates between the two conditions this does not become apparent until the eruption of the secondary dentition. Retinal pigmentation is an inconsistent feature of were indicated with green frame (Ratbi et al, 2015). The mutation identified in this study was indicated with red frame.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 64%
“…In three previously reported caucasian families with Heimler syndrome due to PEX1 mutations, compound heterozygosity for a previously reported loss of function and a novel missense PEX1 variant was described (Ratbi et al, 2015) (Fig 3b). The patient reported here was homozygous for a novel hypomorphic PEX1 allele similar to that reported in another Moroccan family PEX1 (p.Trp1250*).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 77%
See 3 more Smart Citations